Positive Effects of the Caregiver Skill Training Program on Children With Developmental Disabilities: Experiences From Serbia - Glumbic, Nenad; Grujicic, Roberto; Stupar, Sanja; Petrovic, Suncica; Pejovic-Milovancevic, Milica (Frontiers in Psychiatry, 2022)
Background: Intervention programs for children with developmental disabilities increasingly target caregiver training to implement effective strategies for child development. Research conducted in different countries shows that the Caregiver Skills Training Program (CST) developed by the World Health Organization and Autism Speaks could also be a recommended intervention. Methods: The pre-pilot phase included seven, and the pilot phase included 29 families of children with developmental disabilities trained to implement the intervention program. The caregivers were asked to complete the Autism Treatment Evaluation Checklist at the beginning and at the end of the program. Results: In the pre-pilot phase, the Wilcoxon signed-rank test determined a statistically significant improvement in Speech, Language and Communication (z=-2.99, p˂0.05) and Health/Physical/Behaviour (z=-2.375, p˂0.05) after caregiver participation in the training program. In the pilot phase, the paired t-test also determined a statistically significant improvement in Speech, Language and Communication between the first (M=24.52, SD=5.57) and the second testing (M=25.66, SD=6.11), t(28) = - 2.29, p ˂ 0.05, as well as a significant improvement between the first (M=36.62; SD=7.15) and the second testing (M=35.38; SD=5.91), t(28) = 2.11, p ˂ 0.05 in Health/Physical/Behaviour. Eta squared values (0.16 and 0.14) indicate that the intervention effect was significant. No differences were determined in Sociability and Sensory/Cognitive Awareness between the first and the second testing. Conclusion: The initial results of the Caregiver Skills Training Program are encouraging. For this program to be recommended as an evidence-based intervention, further research should be conducted on larger samples, controlling possible intervening variables.